Identification of a functioning mitochondrial uncoupling protein 1 in thymus - Fallon, Padraic; Porter, Richard (My University, 2005)
We present evidence that rat and mouse thymi contain mitochondrial uncoupling protein (UCP 1). Reverse transcriptase-PCR detected RNA transcripts for UCP 1 in whole thymus and in thymocytes. Furthermore, using antibodies to UCP 1 the protein was also detected in mitochondria isolated from whole thymus and thymocytes but not in thymus mitochondria from UCP 1 knock-out mice. Evidence for functional UCP 1 in thymus mitochondria was obtained by a comparative analysis with the kinetics of GDP binding in mitochondria from brown adipose tissue. Both tissues showed equivalent Bmax and KD values. In addition, a large component of the nonphosphorylating oxygen consumption by thymus mitochondria was inhibited by GDP and subsequently stimulated by addition of nanomolar concentrations of palmitate. UCP 1 was purified from thymus mitochondria by hydroxyapatite chromatography. The isolated protein was identified by peptide mass mapping and tandem mass spectrometry by using MALDI-TOF and LC-MS/MS, respectively. We conclude that the thymus contains a functioning UCP 1 that has the capacity to regulate metabolic flux and production of reactive oxygen-containing molecules in the thymus.
PUBLISHED
Keywords: Clinical Medicine